2016
DOI: 10.1016/j.lfs.2016.08.033
|View full text |Cite
|
Sign up to set email alerts
|

Development of risperidone liposomes for brain targeting through intranasal route

Abstract: The present paper is aimed at development of functionalized risperidone liposomes for brain targeting through nasal route for effective therapeutic management of schizophrenia. The risperidone liposomes were prepared by thin film hydration method. Various parameters such as lipid ratio and lipid to drug ratio were optimized by using Design-Expert(®) Software to obtain high entrapment with minimum vesicle size. The surface of the optimized liposomes was modified by coating stearylamine and MPEG-DSPE for enhance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
55
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(57 citation statements)
references
References 34 publications
2
55
0
Order By: Relevance
“…Moreover, the fluorescence microscopy studies revealed that the PEG-PLA particles were able to cross the rat's nasal epithelium to the brain [112]. Another study reported that PEGylated liposomes had shown greater uptake of risperidone into the brain in comparison to liposomes and cationic liposomes [113].…”
Section: Pharmaceutical Factors Of the Influence Of Nanoparticles On mentioning
confidence: 99%
“…Moreover, the fluorescence microscopy studies revealed that the PEG-PLA particles were able to cross the rat's nasal epithelium to the brain [112]. Another study reported that PEGylated liposomes had shown greater uptake of risperidone into the brain in comparison to liposomes and cationic liposomes [113].…”
Section: Pharmaceutical Factors Of the Influence Of Nanoparticles On mentioning
confidence: 99%
“…Direct and brain-targeted drug delivery may allow enhanced therapeutic effects even at a lower drug dose, allow rapid drug absorption at the target site, avoid first-pass elimination, and reduce toxicity (Lalani et al., 2014 ; Gomes et al., 2018 ). Several studies on piperine (Elnaggar et al., 2015 ), tarenflurbil (Muntimadugu et al., 2016 ), risperidone (Narayan et al., 2016 ), glycyrrhizic acid (Ahmad et al., 2019 ) and alginate (Haque et al., 2014 ) have substantiated the theory of nose-to-brain delivery systems. UPLC/ESI-Q-ToF-MS/MS based bioanalytical method was developed and validated for pharmacokinetics, biodistribution, brain-targeting efficiency and brain drug-targeting potential studies post intranasal (i.n.)…”
Section: Introductionmentioning
confidence: 96%
“…Their surface can be easily modified to provide them with multiple functions [17]. This has already been demonstrated for improvement of intranasal delivery [18] of rivastigmine [19,20], donepezil [21], zolmitriptan [22].…”
Section: Introductionmentioning
confidence: 99%